Adam, Satan, and the King of Tyre : the interpretation of Ezekiel 28:11-19 in late antiquity - Patmore, Hector M. (Leiden ; Boston : Brill, 2012)
The oracle against the King of Tyre, found in Ezekiel 28.12-19, is a difficult text that inspired diverse interpretations in Late Antiquity. This book examines those interpretations and seeks to understand their origins and development.
Chapter Five The SeptuagintIntroduction to the Source; History of the Source; Textual Matters; Analysis of Text; Summary and Conclusions; Chapter Six The Hebrew Text; Introduction to the Source; History of the Source; Textual Matters; Analysis of Text; Summary and Conclusions; Chapter Seven Conclusion; Resources, Editions, and Translations; General Bibliography; Author Index; Index of Primary Sources.
Includes bibliographical references and indexes.
Master record variable field(s) change: 630
Keywords: Bible. -- Criticism, interpretation, etc; RELIGION -- Biblical Studies -- Prophets; Electronic books